Application of microreactor technology to dehydration of bio-ethanol. (16th January 2021) - Suerz, Rossana; Eränen, Kari; Kumar, Narendra; Wärnå, Johan; Russo, Vincenzo; Peurla, Markus; Aho, Atte; Yu. Murzin, Dmitry; Salmi, Tapio
Highlights: Heterogeneous catalysts for ethene and diethyl ether formation from ethanol were screened. The role of active sites in the product distribution was revealed. Very precise kinetic data were produced in a microreactor device. It was demonstrated that microreactors are strong tools in the study of gas-phase kinetics and catalyst stability. Abstract: Dehydration and etherification of bio-ethanol was studied in a microreactor using γ-alumina, H-Beta-38 and Sn-Beta-38 as catalysts. An extensive series of kinetic experiments was carried out in the microreactor device operating at ambient pressure and temperatures 225–325 °C. The H-Beta-38 catalyst coated microplates exhibited the highest production rate of ethene. While the fresh H-Beta-38 catalyst allowed complete conversion of ethanol and 98% selectivity towards ethene, the catalyst deactivated significantly with time-on-stream. Diethyl ether was the dominating co-product, whereas trace amounts of acetaldehyde were detected in the experiments. Based on the kinetic studies, thermodynamic analysis and catalyst characterization results obtained with SEM-EDX, TEM, nitrogen physisorption, FTIR-Pyridine and white light confocal microscopy, a surface reaction mechanism was proposed. The fundamental hypothesis of the reaction mechanism was the co-existence of two kinds of active sites on the catalyst surface, namely the Brønsted sites promoting dehydration and the Lewis sites responsible for etherification. The Brønsted sites deactivate, whereas the Lewis sites are more stable, which leads to a shift of the product distribution during long-term experiments, from ethene to diethyl ether. The rate equations were implemented in the microreactor model. The kinetic and adsorption parameters included in the model were estimated by non-linear regression analysis. The experimental data were satisfactorily described by the proposed mechanism. The work demonstrated that microreactors are strong tools in the determination of catalytic kinetics and catalyst durability.